2023
DOI: 10.5397/cise.2022.01067
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency in arthroscopic shoulder surgery: a systematic review

Abstract: BackgroundRadiofrequency has seen an increase in use in orthopedics including cartilage lesion debridement in the hip and knee as well as many applications in arthroscopic shoulder surgery. The purpose of this systematic review is to evaluate the safety and usage of radiofrequency in the shoulder.MethodsThis systematic review was registered with PROSPERO (international registry) and followed the preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) guidelines. Embase and PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Studies investigating the effect of RFE on the joint environment are hindered as the temperature profile and depth of penetration following RFE exposure vary significantly with the device used, the ablation settings, the flow of irrigation fluid, and the application technique. 30 This makes it difficult to make reliable comparisons between the studies and assess their relevance to clinical practice, as there is no standardized technique or instrument setting established. Additionally, much of the published literature focuses on the early first-generation RF devices, and there are limited data evaluating the effects of exposure to modern plasma RF instruments on chondrocyte and matrix viability.…”
Section: The Role Of Rf In Cartilage Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the effect of RFE on the joint environment are hindered as the temperature profile and depth of penetration following RFE exposure vary significantly with the device used, the ablation settings, the flow of irrigation fluid, and the application technique. 30 This makes it difficult to make reliable comparisons between the studies and assess their relevance to clinical practice, as there is no standardized technique or instrument setting established. Additionally, much of the published literature focuses on the early first-generation RF devices, and there are limited data evaluating the effects of exposure to modern plasma RF instruments on chondrocyte and matrix viability.…”
Section: The Role Of Rf In Cartilage Pathologymentioning
confidence: 99%
“…More recently, 85 RFE knee chondroplasties assessed 2 years postoperatively identified no complications related to thermal injury, with the functional outcome being correlated with the quality of chondral and meniscal tissue at the time of surgery. 33 Similarly, a systematic review 30 of 63 studies investigating RFE in shoulder arthroscopy concluded that the technology represents a more efficacious and economic treatment than traditional therapies; however, practitioners should be cognizant of the potential for thermal injuries.…”
Section: The Role Of Rf In Cartilage Pathologymentioning
confidence: 99%
See 1 more Smart Citation